Islamophobia and the Challenges of Muslims in Contemporary Eropean Union Countries: Case Studies from Austria, Belgium, and Germany - Muhammad Wildan; Fatimah Husein (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2021)
In the last two decades, the Muslim population in Western Europe has grown in unprecedented ways. At the broader regional level, there are approximately 25 million Muslims living in European Union member states as of 2016, which is estimated to increase to 35 million by 2050. The arrival of Muslims from various countries in the Middle East, Africa, and the Balkans has brought about significant changes and issues socially, economically, as well as politically. Undeniably, some phenomena of discrimination and Islamophobia arise in almost all EU countries in various aspects of public life such as hijâb clothing, building mosques, and housing. Using a qualitative approach and field research, this article explores not only the historical accounts of the presence of Islam in several EU countries, but also the relations between Islam and the state. This research presents several cases of discrimination and Islamophobia and the internal dynamics within the Muslim communities as to the challenges of living in completely different atmosphere. Three countries, namely Austria, Belgium, and Germany are chosen to represent European Union countries. This study contributes to the discourse on the integration of Muslims in European culture and to the way EU countries could involve Muslims in constructing European Islam.